2023
DOI: 10.1021/acsomega.3c00492
|View full text |Cite
|
Sign up to set email alerts
|

Facile Process for the Development of Antiviral Cotton Fabrics with Nano-Embossed Copper Oxide

Abstract: Metallic or metal oxide-based nanoparticles have the potential to inactivate viruses. Among various metals, copper has shown edge over others. One of the rapidly evolving areas is to combine nanoscience for production of self-sanitizing antiviral surfaces. In this study, we designed antiviral-coated fabrics to combat the spread of viruses. Copper oxide nanoparticles were sonochemically synthesized and subsequently deposited using the dip-coat process to modify the surface of fabric. The morphology and structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Previous literature reports successful antibacterial and antiviral cotton fabric preparation by coating it with CuO NPs. Their antibacterial properties towards Gram-negative bacteria ( Escherichia coli ) revealed a zone of inhibition halo about 7 mm around the fabric [ 42 ]. Additionally, Turakhia et al showed that even after 30 cycles of washing of CuO NPs–coated cotton fabrics, their antibacterial activity remained constant against tested Gram-positive and Gram-negative bacterial strains [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature reports successful antibacterial and antiviral cotton fabric preparation by coating it with CuO NPs. Their antibacterial properties towards Gram-negative bacteria ( Escherichia coli ) revealed a zone of inhibition halo about 7 mm around the fabric [ 42 ]. Additionally, Turakhia et al showed that even after 30 cycles of washing of CuO NPs–coated cotton fabrics, their antibacterial activity remained constant against tested Gram-positive and Gram-negative bacterial strains [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…By virtue of its strong biocidal activity, low toxicity, and high abundance, copper has garnered immense interest as an antimicrobial coating agent for decades. Between 2008 and 2011, the US Environmental Protection Agency (EPA) registered over 300 copper alloys as antimicrobials, and their effectiveness against the coronavirus was also recommended in 2021, emphasizing the great potential of copper-containing materials in the manufacturing of self-disinfecting surfaces. Copper nanoparticle (Cu NP)-coated or -impregnated fabrics and textiles have also been explored for potential applications to prevent infection transmission. Nonetheless, the colored metallic copper and Cu­(II)-containing compounds usually require a long contact time of up to hours to eliminate the target, rendering them of limited value in mitigating the lateral transmission of highly infectious pathogens. , In contrast, many earlier studies have shown that the colorless copper­(I) iodide (CuI) exhibits prominent antimicrobial activity and low toxicity that may serve as a more suitable coating precursor. , Most existing methods for CuI coating fabrication, unfortunately, require toxic acetonitrile as the processing solvent due to its poor solubility in other solvent systems . Extensive use of acetonitrile may cause health problems to the workers and a severe impact on the environment.…”
Section: Introductionmentioning
confidence: 99%